Interactive Student Worksheet Based on a Scientific Approach to Understanding Economic Concepts and Critical Thinking - Prihatin Sulistyowati; Maria Ratnawati Surti Ola (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to develop interactive student worksheets based on a scientific approach for primary school students on the topic of ‘Economic Activities.’ Using the ADDIE model, the worksheets were validated by subject matter, language, and media experts. Data was collected through expert validation and practicality questionnaires from students and teachers. The pilot study involved 22 students and 1 instructor, and data analysis was conducted quantitatively. The results showed that the worksheets were highly feasible and practical, with expert validation scores of 96.5% for content, 94.75% for media, and 81% for language, and practicality scores of 86.28% from students and 80.61% from teachers. The pretest and posttest results indicated an improvement in students' scores from 61.8 to 82.7, with an N-Gain score of 0.6% (57.1%). This study highlights the effectiveness of interactive worksheets in improving students' understanding of economic concepts and critical thinking skills.